How does the usage of derivatives affect bank profitability? : the U.S. case - Conceição, Cátia Sofia Pinto da (2019)
The present Dissertation examines banks that are derivatives’ users and analyzes whether the extent of usage has a positive impact on said banks’ profitability. Specifically, it focuses on the impact of the total notional amount of derivatives on banks’ net income, as well as other control variables relevant for the analysis of bank profitability. Accordingly, it employs a fixed effects model on a sample of 282 United States’ banks, over the period 2005-2017. This period includes the U.S. ‘Subprime’ Crisis period, which is quite important in the analysis of U.S. bank profitability. Using the above-mentioned methodology and timeline, the conclusion is that bank profitability is negatively affected by the increment in the notional amount of derivatives’ contracts. Moreover, size, net loans and leases to total deposits ratio, and capital to assets ratio contribute positively for bank profitability. As expected, banks’ net income is typically lower during the crisis window. Moreover, when distinguishing between three types of derivatives – i.e. interest rate, foreign currency and equity, commodity and others, the results are somewhat mixed. The findings for interest rate derivatives are in line with those for the entire sample, as the increase of its use is deleterious for U.S. banks’ profitability. However, where the case of foreign currency derivatives and equity, commodity and other types of derivatives is concerned, this relationship is positive, as an increase in the notional amount of these latter types of derivatives leads to higher bank profitability.